Diagnosis Bias and its Revelance During the Diagnosis Process - Esteban-Zubero, Eduardo; Valdivia-Grandez, Mario Antonio; Alatorre-Jimenez, Moises Alejandro; Torre, Lourdes del Carmen Rizo-De La; Marin-Medina, Alejandro; Alonso-Barragan, Sara Anabel; Arturo, Carlos (Archives of Clinical and Medical Case Reports, 2017)
Diagnosis bias occurs when the diagnosis is not intentionally delayed (the physician do not have the sufficient information available), after an error, or missed to evaluate some information provided (it may occurs due to it could be the first time that the physician try to diagnose the pathology). It may be clasified in cognitive errors, with different subtypes (including cognitive biases, heuristic, diagnostic anchoring, player’s fallacty, satisfaction bias, confirmation bias, outcome bias, retrospective distortion, and overconfidence), and affective influences. Both of them may occur in the two different diagnostics models: Model 1, based on an intuitive and automatic process that requires little cognitive ability; and model 2, a reflexive and analytical process that requires great cognitive ability. However, in the clinical practice, a mix of them is generally used. Diagnosis bias are important because it has been estimated an error rate in a range from 0.6% to 12%. In addition, the adverse effects generated by diagnostic errors have been estimated to range from 6.9% to 17%. The purpouse of this review is to improve the knowledge about diagnosis bias, the awareness of them, and provide adequate ways to avoid them.